Reduction in parvalbumin expression not loss of the parvalbumin-expressing GABA interneuron subpopulation in genetic parvalbumin and shank mouse models of autism. Issue 1 (December 2016) - Filice, Federica; Vörckel, Karl; Sungur, Ayse; Wöhr, Markus; Schwaller, Beat
Abstract Background A reduction of the number of parvalbumin (PV)-immunoreactive (PV+ ) GABAergic interneurons or a decrease in PV immunoreactivity was reported in several mouse models of autism spectrum disorders (ASD). This includesShank mutant mice, withSHANK being one of the most important gene families mutated in human ASD. Similar findings were obtained in heterozygous (PV+/-) mice for thePvalb gene, which display a robust ASD-like phenotype. Here, we addressed the question whether the observed reduction in PV immunoreactivity was the result of a decrease in PV expression levels and/or loss of the PV-expressing GABA interneuron subpopulation hereafter called "Pvalb neurons". The two alternatives have important implications as they likely result in opposing effects on the excitation/inhibition balance, with decreased PV expression resulting in enhanced inhibition, but loss of the Pvalb neuron subpopulation in reduced inhibition. Methods Stereology was used to determine the number of Pvalb neurons in ASD-associated brain regions including the medial prefrontal cortex, somatosensory cortex and striatum of PV-/-, PV+/-, Shank1 -/- andShank3B -/- mice. As a second marker for the identification of Pvalb neurons, we usedVicia Villosa Agglutinin (VVA), a lectin recognizing the specific extracellular matrix enwrapping Pvalb neurons. PV protein andPvalb mRNA levels were determined quantitatively by Western blot analyses and qRT-PCR, respectively. Results Our analyses of total cell numbers in different brain regions indicated that the observed "reduction of PV+ neurons" was in all cases, i.e., in PV+/-, Shank1 -/- andShank3B -/- mice, due to a reduction inPvalb mRNA and PV protein, without any indication of neuronal cell decrease/loss of Pvalb neurons evidenced by the unaltered numbers of VVA+ neurons. Conclusions Our findings suggest that the PV system might represent a convergent downstream endpoint for some forms of ASD, with the excitation/inhibition balance shifted towards enhanced inhibition due to the down-regulation of PV being a promising target for future pharmacological interventions. Testing whether approaches aimed at restoring normal PV protein expression levels and/or Pvalb neuron function might reverse ASD-relevant phenotypes in mice appears therefore warranted and may pave the way for novel therapeutic treatment strategies.